The development of a fabric retrieval system: using a similarity modelling approach. (17th December 2007) - Shieh, M.D.; Cheng, C.C.; Sun, Y.N.
A fabric retrieval system, trained by the Back-Propagation Network (BPN), has been implemented. The new implementation of the retrieval system focuses primarily on the similarity in judgement of a human being's Kansei for fabric images. The colour composition information is quantised and used to index the colour features of each fabric image. The colour features and the corresponding Kansei features are trained using a Neural Network (NN) model. The new similarity modelling approach, which integrates colour features and a human being's perception features into a NN training model, can be further extended to costume fashion design, product styling design, etc.